Understanding the Interaction of Nanopesticides with Plants - Santiago, Etenaldo F.; Pontes, Montcharles S.; Arruda, Gilberto J.; Caires, Anderson R. L.; Colbeck, Ian; Maldonado-Rodriguez, Ronald; Grillo, Renato [UNESP] (Springer Nature, 2020)
Understanding the interactions between engineered nanomaterials and the environment is essential for unbiased assessments of their agricultural applications. Nano-based pesticides can potentially be safer and/or more efficient than their conventional analogs. However, there is limited information about how nanopesticides influence physiology and metabolism during their interactions with plants, particularly, related to its mode of action. The main question herein is about the interaction between nanopesticides and plants. In this chapter, we start from a theoretical discussion on the complex organization of biological systems, offering a variety of examples showing the effects of nanopesticides from uptake to the mode of action. Moreover, we discuss different examples, how physiological and metabolic responses can help us to understand the behavior of plants exposed to nano-based pesticides. Finally, we demonstrate that prediction models can be used as a routine tool for monitoring and classifying plant response according to their degree of resistance or tolerance to determined nanopesticide, aiming to understand the specific characteristics of nanopesticides into plant systems.
Keywords: Intelligent plant protectant; Nanoagrochemicals; Nanopesticides; Plant systems; Smart-agromaterials